Biosulfo Fertilizer Development for Horticulture Crops II. The Effect of Phosphate Rock Content and Inoculum Ratio of Biosulfo on P and S Uptake and Yield of Red Onion in Acid and Alkaline Soils - Sudadi Sudadi; Sumarno Sumarno; Jaka Widada (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2011)
Research aimed to study the influence of phosphate rock-sulfur (PRS) content and inoculum ratios of biosulfo on P and S uptake and red onion yield on acid (Alfisol) and alkaline (Vertisol) soils. Two factors evaluated were PRS content (0%, 60%, 80%) and inoculums of A.niger/P.nalgiovensis ratio of biosulfo (0:0, 1:1 and 3:1). As much of 12 kg of soil (Ø 2 mm) mixed thoroughly with biosulfo, basic fertilizer and manure, put into polybag then watering at field capacity moisture content. One bulb of red onion was planted to each polybag and incubated in the green house. The experiments arranged in completely randomized design with three replications. Variables observed included P and S uptake, and onion yield. Data analyzed with F test at 5% level of significant followed with DMRT if any significant influences. The result shows that the increases of PRS content as well as A. niger ratio of biosulfo tend to increase P and S uptake, especially on acid Alfisol. Highest P and S uptake and onion yield were achieved with treatment combinations of P80I11, P80I31, and P60 I11 for Alfisol, and P80 I11, P60 I11 and P60 I11 for Vertisol respectively. Keywords: phosphate, rock content, inoculums ratio,P and S uptake, onion yield